The Role of Artificial Intelligence and Information Technology in Promoting Knowledge Management in Business Firms: A Review - Maha Alqahtani; Kholod Alqahtani; Mehmet Sabih Aksoy (International Journal of Engineering and Management Research, 2022)
Knowledge Management appears to be more advanced and sophisticated in the twenty-first century, as a result of the advancement of information technology and artificial intelligence technologies. Several academic and commercial scholars have been studying, exploring, and discussing knowledge management for a long time, owing to the importance of this topic for the success of companies in both the public and private sectors. In addition, many prominent firms throughout the world have used a variety of knowledge management methods to ensure that they remain one step ahead of their competitors in today's highly competitive business environment, including businesses that are constantly looking for methods to improve their knowledge management strategies. There have been some studies undertaken to gain a more in-depth grasp of the most recent research trend in knowledge management procedures and best practices in businesses. This subject, on the other hand, demands deeper examination from a variety of angles. The impact of using Artificial Intelligence (AI) and Information Technology (IT) concepts and techniques on the efficiency of knowledge management in modern businesses, particularly has been overlooked by many prior studies. The current study reviews the role of artificial intelligence and information technology in promoting knowledge management in business firms.